Eradication Of Corruption By Tracing Money Laundering As An Integral Legal System That Can Not Be Separated - Ariman Sitompul (International Asia Of Law and Money Laundering, 2023)
Money laundering can undermine the national economy because it is closely related to confidence of a person or another state in the policy of the state. Money laundering is usually done by mixing illicit money with legitimate money so that legitimate businesses will be less competitive with honest companies, undermine the integrity of financial markets because financial institutions (financial institutions) even those that rely on proceeds of crime can face liquidity dangers; resulting in loss of government control of a country's economic policy resulting lack of confidence of other countries in the policies of the country's government.So that in an effort to eradicate the money laundering and criminal acts such as corruption origin is a unity that can not be separated to combat the evidence system is not clear, not balanced proof techniques and mafia Justice.